The Influence of Disclosure of Islamic Social Reporting, Profitability, and Liquidity on Firm Value in Companies Listed in Jakarta Islamic Index Indonesia Stock Exchange 2016-2019 - Agustina, Ahadiah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2020)
Islamic social reporting is a social reporting that involves not only a holistic expectation of society regarding the role of the companies in the community but also a spiritual perspective. This study examines the influences of Islamic social reporting, profitability (which representated by return on assets), and liquidity (which representated by current ratio) to firm value. To measure the extent of Islamic social reporting, the researcher used a checklist that had been specified by AAOIFI (Accounting and Auditing Organization For Islamic Financial Institution) and developed by previous researchers. This study used purposive sampling method from companies listed in Jakarta Islamic Index (JII) during 2016-2019. There are 16 companies which fulfill the criteria as the research samples. The samples data in this study analyzed using multiple linear regression method. The result indicated that Islamic social reporting, profitability (which representated by return on assets), and liquidity (which representated by current ratio) have positif and siginificant effect simultaneously to firm value. While partially, Islamic social reporting has positive but not significant effect to firm value, profitability (which representated by return on assets) has positive and significant effect to firm value, and liquidity (which representated by current ratio) has positive and significant effect to firm value, these are because the good level of corporate profitability and liquidity reflect good financial performance, so that investor perceptions will increase and ultimately will also increase the firm value.